Exercise Improves Redox Homeostasis and Mitochondrial Function in White Adipose Tissue - Leonardo Matta; Caroline Coelho de Faria; Dahienne F. De Oliveira; Iris Soares Andrade; Niedson Correia Lima-Junior; Bianca Martins Gregório; Cristina Maeda Takiya; Andrea Claudia Freitas Ferreira; José Hamilton M. Nascimento; Denise Pires de Carvalho; Alexander Bartelt; Leonardo Maciel; et al. (MDPI AG, 2022)
Exercise has beneficial effects on energy balance and also improves metabolic health independently of weight loss. Adipose tissue function is a critical denominator of a healthy metabolism but the adaptation of adipocytes in response to exercise is insufficiently well understood. We have previously shown that one aerobic exercise session was associated with increased expression of antioxidant and cytoprotective genes in white adipose tissue (WAT). In the present study, we evaluate the chronic effects of physical exercise on WAT redox homeostasis and mitochondrial function. Adult male Wistar rats were separated into two groups: a control group that did not exercise and a group that performed running exercise sessions on a treadmill for 30 min, 5 days per week for 9 weeks. Reactive oxygen species (ROS) generation, antioxidant enzyme activities, mitochondrial function, markers of oxidative stress and inflammation, and proteins related to DNA damage response were analyzed. In WAT from the exercise group, we found higher mitochondrial respiration in states I, II, and III of Complex I and Complex II, followed by an increase in ATP production, and the ROS/ATP ratio when compared to tissues from control rats. Regarding redox homeostasis, NADPH oxidase activity, protein carbonylation, and lipid peroxidation levels were lower in WAT from the exercise group when compared to control tissues. Moreover, antioxidant enzymatic activity, reduced glutathione/oxidized glutathione ratio, and total nuclear factor erythroid-2, like-2 (NFE2L2/NRF2) protein levels were higher in the exercise group compared to control. Finally, we found that exercise reduced the phosphorylation levels of H2AX histone (γH2AX), a central protein that contributes to genome stability through the signaling of DNA damage. In conclusion, our results show that chronic exercise modulates redox homeostasis in WAT, improving antioxidant capacity, and mitochondrial function. This hormetic remodeling of adipocyte redox balance points to improved adipocyte health and seems to be directly associated with the beneficial effects of exercise.